2017
DOI: 10.1002/mds.27124
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian safety in patients with Parkinson's disease: A case‐control study

Abstract: Background Patients with Parkinson’s disease (PD) experience debilitating motor symptoms as well as non-motor symptoms, such as cognitive dysfunction and sleep disorders. This constellation of symptoms has the potential to negatively influence pedestrian safety. Objective Investigate the association of motor symptoms, daytime sleepiness, impaired vigilance, and cognitive dysfunction on pedestrian behavior in patients with PD and healthy older adults. Methods: Fifty PD and 25 control participants were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Studies conducted in the past, that explored pedestrian safety and attention, either did not include light 1417 or concentrated on the impact of other factors, for instance smartphone use 18,19 or traffic lights. 20 To our knowledge, only Burtt 21 focused on such a relationship between light and attention in night-time outdoor conditions, in a study performed and reported over a hundred years ago and not replicated since.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the past, that explored pedestrian safety and attention, either did not include light 1417 or concentrated on the impact of other factors, for instance smartphone use 18,19 or traffic lights. 20 To our knowledge, only Burtt 21 focused on such a relationship between light and attention in night-time outdoor conditions, in a study performed and reported over a hundred years ago and not replicated since.…”
Section: Introductionmentioning
confidence: 99%